Systematic review and meta-analysis of type B aortic dissection involving the left subclavian artery with a Castor stent graft - Yao, Shihua; Chen, Xu; Liao, Yalin; Ding, Gangbing; Li, Dagang; Qin, Gengliang; Qiao, Ruiguo; Sun, Xin; Zheng, Qijun (Frontiers in Cardiovascular Medicine, 2022)
Objective: Despite the rapid development of thoracic endovascular aortic repair (TEVAR), it is still a challenge to maintain the blood flow of the branch arteries above the aortic arch in the case of Stanford type B aortic dissection involving the left subclavian artery (LSA). The Castor stent graft is an integrated, customized, single-branch stent that enables the reconstruction of the LSA. The purpose of this systematic review and meta-analysis was to assess the efficacy of the Castor stent graft for type B aortic dissection. Methods: An extensive electronic literature search (PROSPERO registration number: CRD42022322146) was undertaken to identify all articles published up to August 2022 that described thoracic aortic repair with branch stents in the treatment of type B aortic dissection involving the LSA. The quality of the included studies was analyzed using the MINORS criteria. Results: Eleven studies with 415 patients were eligible for this meta-analysis. The LSA was successfully preserved in all procedures. The technical success rate was 97.5% (95% CI: 0.953-0.991); the intraoperative endoleak rate was 0.1% (95% CI: 0.000-0.012); the intraoperative LSA patency rate was 99.52%; the intraoperative LSA stent deformation and stenosis rate was 0.15% (95% CI: 0.000-0.051)；the early type I endoleak rate was 1.6% (95%CI: 0.003-0.035); the 30-day mortality rate was 0.96%; the early reintervention rate was 2.3% (95% CI: 0.000-0.075); and the perioperative stroke rate was 0% (95% CI: 0.000-0.005). The 1-year survival rate was 99.7% (95% CI: 0.976-1.000). The half-year LSA patency rate was 99.3%, the 1-year LSA patency rate was 97.58%, the 2-year LSA patency rate was 95.23%. During the follow-up period, the leakage rate was 0.3% (95% CI: 0.000-0.017), the incidence of left upper extremity ischemia rate was 0.5% (95% CI: 0.000-0.035), and the deformation and stenosis rate of the LSA stent was 2.2% (95% CI: 0.06-0.046). Conclusions: This meta-analysis demonstrates that endovascular repair of type B aortic dissection using the Castor stent-graft is technically feasible and effective. Castor stent-graft technology has high technical success rate, good short-term and medium-term vascular patency rates, lower stroke rate and mortality rate, and lower left upper extremity ischemia rate.